1997
DOI: 10.1152/jn.1997.77.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Neuronal Activity in the SMA and the Ventral Cingulate Cortex During Prehension in the Monkey

Abstract: Two monkeys were trained to use the thumb and forefinger to lift and hold an instrumented apparatus within a narrow position window for 1 s. The device was equipped to measure the position and the grip and lifting forces exerted by the animal. On blocks of trials the weight and surface texture could be varied or a force-pulse perturbation could be systematically delivered 750 ms after the object entered the window. If unopposed, the perturbation would displace the hand from the position window, and in preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…They found substantially similar percentages in SMA and in the (combined) PMd and PMv. Cadoret and Smith (1997) found similar activation in SMA and in the ventral cingulate motor area in a prehension task.…”
Section: Introductionmentioning
confidence: 62%
“…They found substantially similar percentages in SMA and in the (combined) PMd and PMv. Cadoret and Smith (1997) found similar activation in SMA and in the ventral cingulate motor area in a prehension task.…”
Section: Introductionmentioning
confidence: 62%
“…During the movement period, the execution of the motor task activates a greater number of motor neurons. Especially, the dynamic feature of the task during this period requires additional motor neurons as well as higher discharge rate of the neurons to overcome the inertia of the movement (Buys et al 1986;Cadoret and Smith 1997;Thickbroom et al 1999), adding complexity to the signal, and correspondingly, increasing the FD (Lutzenberger et al 1995). During the holding period, motor neurons are continuously recruited to maintain the task at a certain level of force.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This expectation was surprisingly not confirmed. Using a similar paradigm of predictable perturbations, we explored the supplementary and cingulate motor areas (Cadoret and Smith 1997), the dorsal and ventral premotor areas (Boudreau et al 2001), and the motor cortex itself (Picard and Smith 1992). Although all of these areas yielded modulated activity patterns related to grasping and lifting as well as reflex-like responses to the perturbation, none of these same areas had any significant amount of anticipatory activity resembling neurons in the cerebellar nuclei and the cerebellar cortex.…”
Section: Anticipatory Activity Elsewhere In the Brainmentioning
confidence: 99%
“…During the past several years, we demonstrated that monkeys also show similar adaptive behaviors when confronted with predictable perturbations. However, single-cell recordings of the neuronal discharge in the primary motor cortex (M1), the supplementary motor cortex (SMA), the dorsal and ventral premotor cortex (PMd and PMv), and the cingulate motor area (CMA) related to anticipation of a predictable perturbation has so far failed to find any strong evidence of activity related to these preparatory behaviors (Boudreau et al 2001;Cadoret and Smith 1997;Picard and Smith 1992). To date, the only region where we have found specific anticipatory activity is in cells of the paravermal and hemispheric cerebellar cortex (Dugas and Smith 1992).…”
mentioning
confidence: 99%